Kesalahan peserta didik dalam menyelesaikan soal cerita SPLDV terintegrasi islam berdasarkan teori Newman peserta didik SMP kelas VIII ditinjau dari perbedaan gender - Hidayati, Siti (Maliki Interdisciplinary Journal, 2024)
In a qualitative approach, this study uses qualitative descriptive methods to assess errors that arise when students solve SPLDV story problems that are connected to Islamic values in grade VIII. This study draws on Newman's theory and considers gender differences by involving one male participant and one female participant. Data was collected through tests and interviews, using story description tests and interview sheets. The validity of the data is ensured through triangulation techniques. The results identified three types of errors: lack of understanding by 50%, process skills by 100%, and notation writing by 100%. Misconception is caused by a lack of understanding of the information in the problem. Errors in process skills are caused by the difficulty of applying proper procedures and correct mathematical operations. At the stage of writing the notation, errors occur due to a mismatch between the conclusions written by participants and the final answer obtained.